Regional factors and ICT in university-industry collaboration in Malaysia - Abdul Wahab, Ahmad Fauzi (2006)
One of the most documented consequences of ICT is the trend of decentralisation (of workplace), as reflected by teleworking, etc. ICT is connected to decentralisation for its ability to overcome geographical distance, take advantage of time compression, and restructure business relationships. Organisational and spatial forms of activities were becoming less determined by physical locational factors (distance, centrality, time, and costs). While the location of the organisations and the impact of ICT has become a subject of interest to researchers in the manufacturing firms and other service sectors, empirical study and investigation concerning university location is few. This research investigate whether the location of the universities' facilities are still important to university-industry collaboration and users' interaction."